'Hangry' Drosophila: food deprivation increases male aggression. (July 2021) - Edmunds, Danielle; Wigby, Stuart; Perry, Jennifer C.
Abstract : Aggressive interactions are costly, such that individuals should display modified aggression in response to environmental stress. Many organisms experience frequent periods of food deprivation, which can influence an individual's capacity and motivation to engage in aggression. However, because food deprivation can simultaneously decrease an individual's resource-holding potential and increase its valuation of food resources, its net impact on aggression is unclear. Here, we tested the influence of increasingly prolonged periods of adult food deprivation on intermale aggression in pairs of fruit flies, Drosophila melanogaster . We found that males displayed increased aggression following periods of food deprivation longer than a day. Increased aggression in food-deprived flies occurred despite their reduced mass. This result is probably explained by an increased attraction to food resources, as food deprivation increased male occupancy of central food patches, and food patch occupancy was positively associated with aggression. Our findings demonstrate that aggressive strategies in male D. melanogaster are influenced by nutritional experience, highlighting the need to consider past nutritional stresses to understand variation in aggression. Highlights: Limited food can lower resource-holding potential and raise resource valuation. The net impact of food deprivation on aggression is unclear. We found that adult food deprivation increases aggression in male fruit flies. Deprived males occupied food for longer, which related to higher aggression. Dietary stress increases aggression, suggesting flies get 'hangry'.